A bent probe excited circular ring antenna above cylindrical reflector radiating circular polarization - Vongsack, Souphanna; Phongcharoenpanich, Chuwong; Kosulvit, Sompol; Wakabayashi, Toshio (My University, 2007)
This paper presents the characteristics of a bent probe excited circular ring antenna above cylindrical reflector radiating circular polarization for the point to point wireless Local Area Network communication system. The proposed antenna is operated at the center frequency of 2.45 GHz. The CST software based on FIT (Finite Integral Techniques) is used as the simulation tool for investigating the antenna characteristics. The probe was shielded by dielectric rod and it is bent to obtain good impedance matching and circular polarization. The simulated results of the return loss, radiation pattern, and axial ratio are presented. The antenna has an impedance bandwidth (2:1 VSWR) of 24.93% that cover the frequency range of 2.089 - 2.684 GHz. The antenna has a unidirectional pattern with maximum gain of 8.88 dBi. The average gain level is 8.18 dBi from simulation. The front-to-back ratio in both E-plane and H-plane is better than 20 dB.
Keywords: Circular polarization; Circular ring; Unidirectional antenna